Thermoplasticity of metallic glasses: Processing and applications. (June 2022) - Sarac, Baran; Eckert, Jürgen
Abstract: Owing to their extremely low shear viscosity and fragility, bulk metallic glasses (BMGs) are envisioned as new net-shaping material replacing conventionally used crystalline metals for various applications. The first part of this review describes the general technique and kinetics of thermoplastic forming. The second part elaborates on the thermal processing capability of metallic glasses from atomic- to meter-scale. The micro-/nano-structure obtained after various quenching rates followed by temperature, time and heating rate dependent thermoplastic forming is described in the third section. The deformation behavior and flow kinetics of BMGs in terms of composition, mold features, and applied conditions are elaborated in the fourth section. The variation of volume and enthalpy at the supercooled liquid region, strength retention of metallic glasses compared to other conventional metals and alloys, and kinetics of liquid fragility are given in the fifth section. Finite element modeling and molecular dynamics simulations of high-temperature deformation in BMGs are presented in the sixth part. Thermally-formed BMGs used for different applications, including energy, biomedical and micro-optics, are presented in the final part. Altogether, this review provides an overview of shaping capabilities and modifications in the macro-scale properties and short-to-medium range order of BMGs upon thermoplastic forming.